2017
DOI: 10.2967/jnumed.117.200048
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-NOTA-Functionalized Ubiquicidin: Cytotoxicity, Biodistribution, Radiation Dosimetry, and First-in-Human PET/CT Imaging of Infections

Abstract: Ubiquicidin is an antimicrobial peptide with great potential for nuclear imaging of infectious diseases, as its cationic-rich fragment TGRAKRRMQYNRR (UBI) has been functionalized with NOTA to allow complexation to Ga (Ga-NOTA-UBI). We herein assess the cytotoxicity and radiation dosimetry for Ga-NOTA-UBI and a first-in-human evaluation to diagnose infectious processes. Cytotoxicity was evaluated in green monkey kidney epithelial (Vero) cells and MT-4 leukocytes. Tracer susceptibility was studied in vitro using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 44 publications
1
41
0
Order By: Relevance
“…A pooled meta-analysis of clinical studies with 99m Tc-UBI 29-41 showed 95% sensitivity, 93% specificity and 94% accuracy in various clinical settings including prosthetic infections, diabetic foot infections, fever of unknown origin, osteomyelitis, mediastinitis, and appendicitis [55,64,65]. Due to its ability to discriminate between infection and sterile inflammation, general safety, the lack of side effects [66][67][68][69], and the successful transformation to kit formulations [59,[70][71][72], radiolabelled UBI 29-41 has been proposed as a good candidate for applications in routine imaging [4,9,61]. Nevertheless, prospective multi-centre studies of both 99m Tc-and 68 Ga-UBI 29-41 should still be carried out to achieve robust evidence of the accuracy in clinical imaging of bacterial infections.…”
Section: Imaging Of Infections With Antimicrobial Peptidesmentioning
confidence: 99%
“…A pooled meta-analysis of clinical studies with 99m Tc-UBI 29-41 showed 95% sensitivity, 93% specificity and 94% accuracy in various clinical settings including prosthetic infections, diabetic foot infections, fever of unknown origin, osteomyelitis, mediastinitis, and appendicitis [55,64,65]. Due to its ability to discriminate between infection and sterile inflammation, general safety, the lack of side effects [66][67][68][69], and the successful transformation to kit formulations [59,[70][71][72], radiolabelled UBI 29-41 has been proposed as a good candidate for applications in routine imaging [4,9,61]. Nevertheless, prospective multi-centre studies of both 99m Tc-and 68 Ga-UBI 29-41 should still be carried out to achieve robust evidence of the accuracy in clinical imaging of bacterial infections.…”
Section: Imaging Of Infections With Antimicrobial Peptidesmentioning
confidence: 99%
“…Another approach with gallium-68 was explored by two different groups using [ 68 Ga]gallium-NOTA-UBI-29-41, a synthetic fragment derived from the antimicrobial peptide ubiquicidin that is part of the human first line response towards pathogens. The radiopharmaceutical had already been successfully explored labelled with techenetium-99m and was able to differentiate infection from sterile inflammation and tumours, both in vitro and in vivo, in both animals and humans [32,44,51,65], presumably the cationic antimicrobial peptide fragments interact electrostatically with anionic parts of the bacterial membrane [32,51].…”
Section: Resultsmentioning
confidence: 99%
“…No information is provided on the bacterial strains involved or if any bacteria was cultured at all, because all diagnoses of infection were based on other imaging modalities like bone scintigraphy and white-blood-cell scintigraphy. Authors also concluded that the method is promising, but with the need for further evaluation [32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptides, which are smaller constructs than antibodies, typically offer improved biodistribution for in vivo studies. This has been recently proven by Ebenhan et al with a first in-human study of 68 Ga-NOTA functionalised ubiquicidin (UBI29-41), a cationic-rich peptide with high affinity for fungal cells [104]. Initial assays assessed the performance of the tracer in vitro using different bacterial and fungal strains, followed by PET/CT-imaging biodistribution and pharmacokinetics studies on non-human primates.…”
Section: Alternative Modalities For Non-optical In Vivo Imagingmentioning
confidence: 99%